Efektivitas Pelayanan Publik dalam Proses Penerbitan Surat Izin Usaha Perdagangan (SIUP) Pada Dinas Penanaman Modal dan PTSP Kota Medan - Muhammad Fazil; Muhammad Husni Thamrin (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The issuance of trading business licenses in Indonesia has not been fully implemented properly in accordance with the objectives of public services. This study aims to describe the effectiveness of public services in the process of issuing trading business licenses at the investment office and PTSP Medan City. The data were analyzed qualitatively by using the theory of effectiveness according to Duncan (Steers 1985:53). From the research results, the issuance of trading business licenses is still not effective because the time for completion of permits exceeds the existing standard time and the socialization carried out is also not fully evenly distributed, but the existing facilities and infrastructure are very supportive as supporting services in the management of trading business permits.